Property cycle index : an indicator to the Malaysian property market - Kuek, Tai Hock (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study attempts to investigate the fluctuations in the Malaysian property market and predict the early signals of property market vulnerability using the property cycle indicator (PCI) with data of monthly basis from 1991M1 to 2013M12 and the employment of the indicator construction method proposed by National Bureau of Economic Research (NBER). The constructed PCI consists of six component series, namely, gross domestic product, consumer sentiment index, foreign direct investment, tourist arrival, domestic share price and the United States share price. Empirical results indicated that the movement of PCI is consistent in advance of Property Sales by Unit Transactions (PSU), suggesting that the PCI has a significant amount of signalling attributes against the PSU. This highlighted the potential ability of the leading indicator to predict the property market outlook using a non-parametric technique of indicator construction and information content from a macroeconomic perspective. Therefore, policymakers, property market players, and investors may consider the use of the property cycle indicator as an early signalling tool to predict the movement of the property market in Malaysia.